Integration Strategies of An International Company - Lin Xiao; Robert Voskerichyan (Communications of International Proceedings, 2022)
Integration and globalization are becoming increasingly important economic development. Currently, no state can they exist in isolation from others without resorting to self-cooperation. The country's activities include foreign trade and foreign policy interaction with other countries. Historically justified and quite strong, they largely determine the economic relations between countries in the process of integration. Integration processes are becoming an integral part of the increasing globalization of the world economy. They represent a qualitatively new form of interstate interaction and have the ultimate goal is to accelerate the pace of economic growth and increase the competitiveness of the countries participating in the integration processes. The problems and priorities of the development of groupings are the subject of research not only by economists, but also by sociologists, historians, and political scientists.
Keywords: component; integration; globalization; international market; strategic; business.